2021
DOI: 10.1007/s12105-021-01341-5
|View full text |Cite
|
Sign up to set email alerts
|

Well-Differentiated Liposarcoma of the Hypopharynx Exhibiting Myxoid Liposarcoma-like Morphology with MDM2 and DDIT3 Co-Amplification

Abstract: Well-differentiated liposarcoma (WDL) is one of the most common soft tissue sarcomas in adults. It has a predilection for middle-aged males and arises in deep-seated locations such as retroperitoneum, mediastinum, and spermatic cord. Its occurrence in young individuals at the hypopharyngeal region is an exceedingly rare event. Myxoid liposarcoma (ML)-like changes can seldom occur in some cases of WDL, which makes the diagnosis of WDL more challenging. Amplification of DDIT3 gene in a subset of cases of WDL has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In such cases, the use of MDM2 and CDK4 by immunohistochemistry and/or FISH is helpful to establish the diagnosis. 13,14 Positive staining for MDM2 and/or CDK4 or the detection of their amplified genes by FISH confirms the diagnosis of WDL. 13,14 It is also essential to extensively sample the tumor to rule out the possibility of dedifferentiated liposarcoma, which is characterized by the presence of highgrade spindle cell sarcoma adjacent to the well-differentiated component.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In such cases, the use of MDM2 and CDK4 by immunohistochemistry and/or FISH is helpful to establish the diagnosis. 13,14 Positive staining for MDM2 and/or CDK4 or the detection of their amplified genes by FISH confirms the diagnosis of WDL. 13,14 It is also essential to extensively sample the tumor to rule out the possibility of dedifferentiated liposarcoma, which is characterized by the presence of highgrade spindle cell sarcoma adjacent to the well-differentiated component.…”
Section: Discussionmentioning
confidence: 86%
“…13,14 Positive staining for MDM2 and/or CDK4 or the detection of their amplified genes by FISH confirms the diagnosis of WDL. 13,14 It is also essential to extensively sample the tumor to rule out the possibility of dedifferentiated liposarcoma, which is characterized by the presence of highgrade spindle cell sarcoma adjacent to the well-differentiated component. 12 It has been found that up to 50% of laryngeal liposarcomas recur; therefore, the current recommendation is to perform wide surgical excision with negative margins.…”
Section: Discussionmentioning
confidence: 86%
“…Well-differentiated and dedifferentiated liposarcomas can contain prominent myxoid stroma, which can present as a diagnostic challenge when confronted with a small biopsy sample. Such tumors have been shown to contain coamplifications of MDM2 and DDIT3 [22][23][24][25], further adding to a potential diagnostic dilemma. Helpful morphologic clues to exclude the presence of a ML would be absence of the characteristic uniform histomorphology with presence of pleomorphic cells/lipoblasts in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The answer was only possible through FISH testing for MDM2 and DDIT3 amplification. DDIT3 amplification appears not to affect the prognosis, including recurrence free survival or disease specific survival, nor the rate of distant metastasis [22][23][24][25]. The role of DDIT3 in the pathogenesis of DDL as a possible driver/non-driver mutation or regulating adipocytic differentiation requires larger studies to further characterize.…”
Section: Discussionmentioning
confidence: 99%